The Role of Neuropeptide Y mRNA Expression Level in Distinguishing Different Types of Depression - Yue, Yingying; Jiang, Haitang; Yin, Yingying; Zhang, Yuqun; Liang, Jinfeng; Li, Shenghua; Wang, Jun; Lu, Jianxin; Geng, Deqin; Wu, Aiqin; Yuan, Yonggui (Frontiers in Aging Neuroscience, 2016)
Previous studies demonstrate that the protein of neuropeptide Y (NPY) is abnormal in depression patients，but the changes of NPY in different types of depression are unclear. This study was aimed to examine protein and mRNA expression levels of NPY in 159 cases with four groups including post-stroke depression (PSD) group, stroke without depression (Non-PSD) group, major depressive disorder (MDD) group and normal control (NC) group. The protein and gene expression analysis were performed by enzyme-linked immunosorbent assay and quantitative polymerase chain reaction-based methods. One way analysis of variance, chi-square tests and nonparametric test were used to evaluate general characteristics, clinical and biological materials. In order to explore the role of NPY in different types of depression, the partial correlations, binary logistic regression analysis and receiver operating characteristic (ROC) curve were calculated for PSD and MDD groups. There are significant differences of NPY protein (Fdf(3)=5.167, P=0.002) and mRNA expression levels (X2Kruskal-Wallis, df(3)=20.541, P<0.001) among four groups. Bonferroni multiple comparisons found that the NPY protein was significantly decreased in PSD (FBonferroni=-7.133, P=0.002) and Non-PSD group (FBonferroni=-5.612, P=0.018) compared with NC group. However, contrasted with MDD group, the mRNA expression was increased in PSD and Non-PSD group by nonparametric test (all P<0.05). In binary logistic analyses, NPY mRNA expression was independent predictors of PSD (odds ratio: 1.452, 95% CI, 1.081-1.951, P=0.013). The ROC curve showed NPY mRNA had a general prognostic accuracy (area under the curve: 0.766, 95% CI, 0.656-0.876, P<0.001). This is the first study to explore the distinguishing function of NPY in different types of depression. It will provide help in the identification of different subtypes of depression.